2022
DOI: 10.1371/journal.pone.0259366
|View full text |Cite
|
Sign up to set email alerts
|

Industrial green total factor productivity in China’s Yangtze River Economic Zone: Temporal and spatial difference analysis based on 108 panel data

Abstract: As China’s strategic support belt, the green development of industry in the Yangtze River Economic Zone is of great significance to promote the construction of China’s ecological civilization, build a modern industrial system and accelerate high-quality economic development. The study of green total factor productivity of industry in the Yangtze River Economic Zone has important theoretical and practical value for exploring the green development path of China’s industry. This Paper takes the Yangtze River Econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Based on the SBM model, Li J. et al (2021) constructed MML index to comprehensively access GTFP on Chinese laying hens (GTCL). A quantitative analysis of the changes in industrial GTFP in the Yangtze River Economic Zone was performed by Zhang et al (2022) using the MML index which takes into account expected and unexpected output.…”
Section: Temporal Heterogeneitymentioning
confidence: 99%
“…Based on the SBM model, Li J. et al (2021) constructed MML index to comprehensively access GTFP on Chinese laying hens (GTCL). A quantitative analysis of the changes in industrial GTFP in the Yangtze River Economic Zone was performed by Zhang et al (2022) using the MML index which takes into account expected and unexpected output.…”
Section: Temporal Heterogeneitymentioning
confidence: 99%
“…Fu et al have also confirmed that technological advancements play a vital role in improving economic growth efficiency and promoting green transformation [25]. Additionally, Zhang's findings have revealed the heterogeneous effects of technical efficiency and technological progress efficiency on different river basins in the upper, middle, and lower reaches of the Yangtze River in China [26]. According to Sun's research, it has been demonstrated that innovation in terms of clean technology has a noteworthy and favorable influence on the overall productivity of green industrial sectors [27].…”
Section: Literature Reviewmentioning
confidence: 94%
“…At present, the research objects focus on traditional administrative regions, ranging from an international perspective to countries, provinces, cities, and locations within the country [19][20][21][22] China's national-level urban agglomerations such as the Yangtze River Delta urban agglomeration and the Beijing-Tianjin-Hebei urban agglomeration have also attracted widespread attention from domestic and foreign scholars [23][24][25] . A small number of regional urban agglomeration studies measure the green development level of cities by calculating specific industries or factors, such as economic factors 26 , agricultural development 26 , and ecological governance 28 , making it difficult to fully reflect the urban agglomeration`s green development condition.…”
Section: Literature Reviewmentioning
confidence: 99%